Review of Proxima DeLong & Freytag (Hemiptera: Cicadellidae: Gyponini) with description of two new species from Brazil and identification key to species - Laranjeira, Vanessa Cristina; Gonçalves, Clayton Corrêa; Domahovski, Alexandre Cruz; Takiya, Daniela Maeda (Zootaxa, 2022)
The previously monotypic genus Proxima DeLong & Freytag, 1975 is reviewed and new diagnostic characters are added. The type-species Proxima ocellata DeLong & Freytag, 1975 described from the State of Espírito Santo, Brazil, is redescribed and newly recorded from the State of Minas Gerais. Also, two new species are described and illustrated: Proxima nigromaculata sp. nov. from the states of Espírito Santo, Maranhão, Minas Gerais, Rio de Janeiro and Rio Grande do Sul and Proxima meloi sp. nov. from the states of Bahia and Minas Gerais. An identification key to the species of the genus is provided.